COVID-19 and Sudden Sensorineural Hearing Loss: A Systematic Review - Meng, Xiangming; Wang, Jing; Sun, Jian; Zhu, Kangxu (Frontiers in Neurology, 2022)
A growing body of evidence suggests that patients with the 2019 Coronavirus disease (COVID-19) have a risk of developing sudden sensorineural hearing loss (SSNHL). The pathogenesis of COVID-19-related SSNHL remains unclear. This systematic review examined whether COVID-19 causes an increased incidence of SSNHL and the clinical characteristics of patients with COVID-19-related SSNHL according to the PRISMA guidelines. SSNHL usually developed between a few days and 2 months after the diagnosis of COVID-19, and a proportion of patients developed it before the diagnosis of COVID-19. The literature is inconsistent regarding whether COVID-19 causes an increased incidence of SSNHL, and this matter remains unclear. This review included 23 patients with COVID-19-related SSNHL, all adult patients with an average of 43.1 years. Of these patients, 60.9% had accompanying tinnitus symptoms. Glucocorticoids are the preferred medication to treat COVID-19-related SSNHL. Intratympanic administration may be considered to reduce the side effects of the drug. Hearing tests are suggested when hearing loss is suspected in COVID-19 individuals; if SSNHL is detected, prompt and aggressive treatment is vital. Large-scale, multicenter research on the pathophysiology, treatment, and prognosis of COVID-19- related SSNHL should be conducted in the future.